Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18632/oncotarget.7953
|View full text |Cite
|
Sign up to set email alerts
|

MiR-148a functions to suppress metastasis and serves as a prognostic indicator in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) presents a major challenge in the clinic due to its lack of reliable prognostic markers and targeted therapies. Accumulating evidence strongly supports the notion that microRNAs (miRNAs) are involved in tumorigenesis and could serve as biomarkers for diagnostic purposes. To identify miRNAs that functionally suppress metastasis of TNBC, we employed a concerted approach with selecting miRNAs that display differential expression profiles from bioinformatic analyses of breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 61 publications
4
45
0
Order By: Relevance
“…Numerous miRNAs have been found to be dysregulated under the pathological condition of NSCLC 18,19. Recently, studies have found that miR-148a functions to suppress NSCLC 2022. However, the mechanism underlying the inhibitory effect of miR-148a on NSCLC is still not completely known.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous miRNAs have been found to be dysregulated under the pathological condition of NSCLC 18,19. Recently, studies have found that miR-148a functions to suppress NSCLC 2022. However, the mechanism underlying the inhibitory effect of miR-148a on NSCLC is still not completely known.…”
Section: Introductionmentioning
confidence: 99%
“…miR-148a was identified by bioinformatic analysis of BC patient databases. There is a correlation between the low expression of miR-148a in higher grade tumors and a higher likelihood to develop metastases and poor prognosis especially in BC patients with basal and luminal B subtypes (94). In 4T1 and MDA-MB-231 BC cells, ectopic expression of miR-148a did not affect cell growth, viability in culture or in vitro migration (94).…”
Section: Breast Cancer Metastasis Suppressing Mirsmentioning
confidence: 99%
“…There is a correlation between the low expression of miR-148a in higher grade tumors and a higher likelihood to develop metastases and poor prognosis especially in BC patients with basal and luminal B subtypes (94). In 4T1 and MDA-MB-231 BC cells, ectopic expression of miR-148a did not affect cell growth, viability in culture or in vitro migration (94). However, for both cell lines there was a reduction of lung metastases (≥50%) observed after fat pad implantation of cells ectopically expressing miR-148a.…”
Section: Breast Cancer Metastasis Suppressing Mirsmentioning
confidence: 99%
See 2 more Smart Citations